IRELAND. SPATIAL DEVELOPMENT OF THE NATIONAL ECONOMY - PAVEL Stroev (Мир новой экономики)
Strategic planning has the major place of the government regulation of economic and social process at modern conditions. The government and regions administrations develop plans and programs that are used as instrument realization politic of management. This plans and programs aid government to reach theircorrect, justified goals.Radical innovations give impact to progressing big economy systems that founded on the growth multiply economy growth theory of innovation type developed on create poles of growth. Technological innovations are the result of generating these radical innovations in special centers, so there is another fresh quality of economy growth. The point of such economy growth consist in formation economic agglomeration near centers either location way or industrial.The leading countries focus special attention on spatial development of the national economic. Russia especially interested in the experience of the leading countries in the sphere of state economy regulation to analyze, adapt and evaluate possibilities to use the decision of problems for the Russian economy.There is analyze of Ireland’s system of strategy planning where especial consider the theme of planning spatial development national economy. The result of the analysis is identification the peculiarities functioning system of strategic planning in Ireland and the definition of the approach to spatial development of Irelandthrough the way to format and promote poles of growth.